2019
DOI: 10.30891/jopar.2018s.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Forms of Spontaneous Psi Experiences

Abstract: In this study, approximately one thousand cases of spontaneous psychic experiences were analyzed to find out what range of forms the experiences more commonly took. Four main types were found: (1) Intuitive, in which the subject's experience was a simple, unreasoned impression or hunch. (2) Hallucinatory, in which the experience was projected as if it were a sensation. (3) Unrealistic dreaming, in which the experience was characterized by fantasy. (4) Realistic dreaming, in which the imagery was almost photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Sometimes related to E-Psi, is the so-called decline effect (DE), which is defined as "the tendency for high scores in a test of psi to decrease, either within a run, within a session, or over a longer period of time" (Thalbourne, 2003, p. 27). The DE is also well documented (Colborn, 2007;Rhine, 1969).…”
Section: Experimenter Psi and The Decline Effectmentioning
confidence: 99%
“…Sometimes related to E-Psi, is the so-called decline effect (DE), which is defined as "the tendency for high scores in a test of psi to decrease, either within a run, within a session, or over a longer period of time" (Thalbourne, 2003, p. 27). The DE is also well documented (Colborn, 2007;Rhine, 1969).…”
Section: Experimenter Psi and The Decline Effectmentioning
confidence: 99%
“…In general, however, systematic research into faculties suggestive of psi in the animal kingdom has largely been neglected. Facets that have been studied comprise the homing behavior of animals (for reviews, see Nahm, 2015;Sheldrake, 2011), cases of "psi trailing" in which an animal found its owner in a new location that the animal had never visited previously (Gaddis & Gaddis, 1970;Rhine & Feather, 1962;Sheldrake, 2011), the ability of animals to anticipate when their owners return, other animal premonitions, animals that "read people's minds" and respond to their intentions, as well as animals' reactions to distant death and danger (e.g., Pleimes, 1971aPleimes, , 1971bSheldrake, 2011;Sheldrake & Morgana, 2003; for an over-view of such studies, see Sheldrake, 2015).…”
Section: Experiences Of Dying Animals: Parallels With End-of-life Exp...mentioning
confidence: 99%
“…From the early days of psychical research, investigation of spontaneous cases tried to establish the objective reality of mind-to-mind contact (Gurney et al, 1886) and precognition (Besterman, 1932-33;Saltmarsh, 1934). Louisa Rhine's analysis of the several thousand unsolicited epistolic accounts submitted to the Rhine laboratory at Duke led to a thematic classification of types of experiences and the conditions in which they occurred (Rhine, 1981(Rhine, , 2018; see also Kelly & Tucker, 2015;Stevenson, 1970). Survey based research has revealed the incidence of subjective paranormal experiences in various populations (Castro et al, 2014;Haraldsson, 1985;Palmer, 1979), and there has been research to identify psychological features, such as associated imagery, vividness, and degree of conviction (Alvarado, 1996).…”
Section: Example 1: Rattled/rattedmentioning
confidence: 99%